2002
DOI: 10.1111/j.1745-9125.2002.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Reporting and Not Reporting Domestic Violence to the Police*

Abstract: The National Crime Victimization Survey is used to examine factors that encourage and inhibit victims of domestic violence from calling the police. Victims of domestic violence are less likely than victims of other types of violence to call the police because of their privacy concerns, their fear of reprisal, and their desire to protect offenders, but they are more likely to call for self‐protection and because they perceive domestic assaults as more serious. As a result of these and other offsetting factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
312
2
16

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(366 citation statements)
references
References 18 publications
23
312
2
16
Order By: Relevance
“…When asked why they had not reported the matter to the police, 36% of the women and 52% of the men felt that it was a private or personal matter, 19% of women were afraid of reprisal, 7% of women and 15% of men felt that it was a minor crime, 6% of women felt that the police would not bother with the incident, and 3% of women and 11% of men felt that the police would protect the offender (Rennison & Welchans, 2000). Felson, Messner, Hoskin, and Deane (2002) used the NCVS data to test specific hypotheses regarding reasons for reporting to police in domestic violence situations compared with other types of violence. They found that victims of domestic violence are more likely to call police for self-protection and perceived assault seriousness, but are less likely to call out of fear of reprisal, privacy concerns, or a desire to protect the offender when compared with other victims of assault.…”
Section: The Role Of Law Enforcementmentioning
confidence: 99%
“…When asked why they had not reported the matter to the police, 36% of the women and 52% of the men felt that it was a private or personal matter, 19% of women were afraid of reprisal, 7% of women and 15% of men felt that it was a minor crime, 6% of women felt that the police would not bother with the incident, and 3% of women and 11% of men felt that the police would protect the offender (Rennison & Welchans, 2000). Felson, Messner, Hoskin, and Deane (2002) used the NCVS data to test specific hypotheses regarding reasons for reporting to police in domestic violence situations compared with other types of violence. They found that victims of domestic violence are more likely to call police for self-protection and perceived assault seriousness, but are less likely to call out of fear of reprisal, privacy concerns, or a desire to protect the offender when compared with other victims of assault.…”
Section: The Role Of Law Enforcementmentioning
confidence: 99%
“…Um estudo realizado nos Estados Unidos constatou que as vítimas de violência doméstica são mais tendentes do que outras vítimas a chamar a polícia pela autopreservação e porque reconhecem os ataques domésticos como mais graves do que outras transgressões (Felson et al, 2002).…”
Section: Profissionais De Saúdeunclassified
“…People may however fear to report crimes because of fear of reprisal from the offenders, embarrassment at having been victimized, fear of reprisal from others in groups where cooperation with governmental officials is looked down upon (Zhang et al, 2007). Another challenge may be the long adjudication process which may discourage victims from reporting serious crimes (Felson et al, 2002).…”
Section: Theoretical Literaturementioning
confidence: 99%
“…According to this approach the victims weigh the potential benefits and costs to be incurred when considering whether to file a complaint about a criminal incident with the police. In most of the cases the benefits of filing a complaint include the victims drive to have the offenders brought to justice through punishment; protection of the victims and potential victims from future victimization (Felson et al, 2002). In the instances of property crimes, the benefits of reporting crimes are also based on the anticipation of recovery of stolen goods.…”
Section: Theoretical Literaturementioning
confidence: 99%
See 1 more Smart Citation